PERISTIWA PERANG KAMANG TAHUN 1908 (GERAKAN RAKYAT KAMANG TERHADAP BELANDA) - Masyitah, Masyitah; Ibrahim, Bedriati; Melay, Ridwan (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The outbreak of war in the early 20th century in western Sumatera was of form of ressistance to taxation (Belasting)byhe the Ducth. Some regions that carried out the ressisten included one of the in Kamang are which was the first area to fight against the Ducth which eventually also caused a similiar reaction in several other area in West Sumatera. The people of Kamang strongly appose the stipulation of Belasting which is very detrimental to the people so thatthe people have planned resistance by devising tactics in facing the Ducth who set policies without asking for gree ment from the pople. The purpose of the study is 1) to know the cause of the war 2) to find out how your war net are 3) to find out how the end of our war in 1908 4)to find out the consequences of the 1908 war. As for this study using qualitative reseach with a historical approach and collection techniques documentation, observationn, and interview.The result of this study indicate that the resistance and resistance to the application of taxes makes both parties decide to attack at night and the killing of the war leader from the Kamang. Peoples anthusiasme in the fighting the Ducth can be seen from the makes shift war equipment the use when dealing with Netherlands.Key Words: Tax, Resistance, Kamang